Chromosome architecture constrains horizontal gene transfer in bacteria. - Heather L Hendrickson; Dominique Barbeau; Robin Ceschin; Jeffrey G Lawrence (PLoS Genetics)
Despite significant frequencies of lateral gene transfer between species, higher taxonomic groups of bacteria show ecological and phenotypic cohesion. This suggests that barriers prevent panmictic dissemination of genes via lateral gene transfer. We have proposed that most bacterial genomes have a functional architecture imposed by Architecture IMparting Sequences (AIMS). AIMS are defined as 8 base pair sequences preferentially abundant on leading strands, whose abundance and strand-bias are positively correlated with proximity to the replication terminus. We determined that inversions whose endpoints lie within a single chromosome arm, which would reverse the polarity of AIMS in the inverted region, are both shorter and less frequent near the replication terminus. This distribution is consistent with the increased selection on AIMS function in this region, thus constraining DNA rearrangement. To test the hypothesis that AIMS also constrain DNA transfer between genomes, AIMS were identified in genomes while ignoring atypical, potentially laterally-transferred genes. The strand-bias of AIMS within recently acquired genes was negatively correlated with the distance of those genes from their genome's replication terminus. This suggests that selection for AIMS function prevents the acquisition of genes whose AIMS are not found predominantly in the permissive orientation. This constraint has led to the loss of at least 18% of genes acquired by transfer in the terminus-proximal region. We used completely sequenced genomes to produce a predictive road map of paths of expected horizontal gene transfer between species based on AIMS compatibility between donor and recipient genomes. These results support a model whereby organisms retain introgressed genes only if the benefits conferred by their encoded functions outweigh the detriments incurred by the presence of foreign DNA lacking genome-wide architectural information.